Using Real Worked Examples to Aid Software Engineering Teaching - Tonhão, Simone; Colanzi, Thelma; Steinmacher, Igor (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2021: Anais do XXXV Simpósio Brasileiro de Engenharia de Software, 2021)
Worked examples are instructional devices composed of the description of a problem, steps to solve the problem, and the final result. There is evidence that the use of the worked examples improves the learning process by reducing the learning time, reducing the cognitive load, and facilitating the construction of cognitive schemes. In addition, students who learn from worked examples tend to solve similar problems more quickly and easily. Worked examples are adopted in several areas of knowledge but are not well-explored in Software Engineering (SE) teaching. Thus, the goal of this work was to explore the use of worked examples in SE courses. To do so, we conducted an exploratory study split into two stages. In the first stage, we administered a survey with SE instructors to investigate the use of common examples, worked examples, and the difficulties find this type of material. In the second stage, we applied worked examples in the classroom and collected feedback from students. The second stage was carried out remotely due to the conditions imposed by COVID-19. The results showed that instructors are employing examples in their courses; some of them use worked examples, even when they do not know the definition. In addition, the feedback from the students was positive, which may encourage the use of worked examples in SE teaching.